Atuação de forças em hastes sulcadoras de semeadoras-adubadoras para plantio direto - Germino, Rogério [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
O sistema de produção agrícola exige tecnologias cada vez mais aperfeiçoadas para seu desenvolvimento sustentável, tendo o sistema plantio direto contribuído diretamente nesse sentido, com o aperfeiçoamento de máquinas e equipamentos que melhor se adaptam as suas condições preliminares de implantação. Nesse quadro, as semeadoras-adubadoras são os equipamentos que sofrem as mais variadas modificações em sua constituição, pois nesse sistema o principio básico é o revolvimento somente na linha de semeadura, fazendo com que esses equipamentos realizem operações conjugadas associando qualidade e otimização dos recursos disponíveis. Uma técnica que vem sendo adotada pelos produtores é a substituição (nas semeadoras) dos discos duplos para deposição de adubos pelas hastes sulcadoras em maiores profundidades, com o objetivo de romper as camadas compactadas de solo, adiando assim o uso de escarificadores e subsoladores. Nesse sentido o presente estudo que foi realizado em condições de campo, com o objetivo de comparar dois modelos de hastes sulcadoras, uma comercial e uma experimental, para semeadoras adubadoras de plantio direto, determinado as forças atuantes e os momentos (Fx: força horizontal, Fy: força vertical, Fz: força lateral, My: momento transversal e Fz: momento longitudinal), variando quatro profundidades de trabalho (130mm, 230 mm, 280 mm e 330 mm) com e sem a utilização de disco de corte de palha. A haste Experimental apresentou maiores valores de força horizontal média (Fx), força vertical média (Fy), força lateral média (Fz), força horizontal máxima (Fx max), força vertical máxima (Fy max), força média por área de solo mobilizado (Fx/ASM), força horizontal específica (Fx esp.) momento transversal médio (My), momento longitudinal médio (Mz), momento transversal máximo (My max)...

The agricultural system demands technologies more and more improved for its sustainable development, and agricultural system called no till has been contributed directly in that sense, with the improvement of machines and equipments that could be used with soil previous coverage. In this way row preparation shank are the equipments that suffer the most varied modifications in your constitution, because the basic concept is to revolve only the furrow, so those equipments have to have conjugated operations in consortium with quality and the improvement of the available resources. A technique that has been adopted by the farmers is the change (in the furrow openers) of the double disks for fertilizers deposition for a row preparation shank in higher depths. The objective of this change is to break the compacted layers of soil, postponing the usage of subsoiler and chisel plow witch are more expensive operations. In that sense the present study was accomplish in field conditions, with the objective of comparing two models of preparation shank for no till system, certain the active forcers and moments (Fx: horizontal force, Fy: vertical forces, Fz: lateral force, My: traverse moment and Mz: longitudinal moment), varying four work depths (130 mm, 230 mm, 280 mm and 330 mm) with and without the use of soil and residue cut disk. The experimental row preparation shank showed higher horizontal medium force values (Fx), vertical medium force (Fy), lateral medium force (Fz), horizontal maximum force (Fx max.), horizontal medium force by disturbed soil area (Fx/DSA), horizontal force by soil depth ( Fx sd) transverse medium moment (My), longitudinal medium moment (Mz), transverse maximum moment (My max.), longitudinal maximum moment (Mz max.), mximum power (P max.) e medium power (Pm). The showed differences ( row preparation shank) are related to their building structure. When we worked at... (Complete abstract click electronic access below)
Keywords: Energia; Plantio direto; Plantadeiras (Maquinas agricolas); Energy; Planters (Agricultural machinery)